Intelligent Algorithms in Ambient and Biomedical Computing - Verhaegh, Wim.; Aarts, Emile; Korst, Jan.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The rapid growth in electronic systems in the past decade has boosted research in the area of computational intelligence. As it has become increasingly easy to generate, collect, transport, process, and store huge amounts of data, the role of intelligent algorithms has become prominent in order to visualize, manipulate, retrieve, and interpret the data. For instance, intelligent search techniques have been developed to search for relevant items in huge collections of web pages, and data mining and interpretation techniques play a very important role in making sense out of huge amounts of biomolecular measurements. As a result, the added value of many modern systems is no longer determined by hardware only, but increasingly by the intelligent software that supports and facilitates the user in realizing his or her objectives. This book is the outcome of a series of discussions at the Philips Symposium on Intelligent Algorithms, which was held in Eindhoven in December 2004. It contains many exciting and practical examples of the use of intelligent algorithms in the areas of ambient and biomedical computing. It contains topics such as bioscience computing, database design, machine consciousness, scheduling, video summarization, audio classification, semantic reasoning, machine learning, tracking & localization, secure computing, and communication.
Healthcare -- Bioscience Computing and the Role of Computational Simulation in Biology -- The Many Strands of DNA Computing -- Bio-Inspired Data Management -- An Introduction to Machine Consciousness -- Lifestyle -- Optimal Selection of TV Shows for Watching and Recording -- Movie-in-a-Minute: Automatically Generated Video Previews -- Features for Audio Classification: Percussiveness of Sounds -- Extracting the Key from Music -- Approximate Semantic Matching of Music Classes on the Internet -- Ontology-Based Information Extraction from the World Wide Web -- Privacy Protection in Collaborative Filtering by Encrypted Computation -- Technology -- A First Look at the Minimum Description Length Principle -- Semantic Web Ontologies and Entailment: Complexity Aspects -- Bayesian Methods for Tracking and Localization -- Private Profile Matching -- Air Fair Scheduling for Multimedia Transmission over Multi-RateWireless LANs -- High Throughput and Low Power Reed Solomon Decoder for Ultra Wide Band.
Keywords: Mathematics; Multimedia information systems; Artificial intelligence; Bioinformatics; Computational biology; Algorithms; Mathematics; Algorithms; Artificial Intelligence (incl. Robotics).; Multimedia Information Systems; Computer Appl. in Life Sciences; Signal, Image and Speech Processing; Electronic books